Perception of the Sagas Of Icelanders in Modern Icelandic Crime Novels - Ольга Александровна Маркелова (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2019)
Olga A.Markelova (Moscow, Russian Federation)